A complex estimation of the new variety of peas ‘Uldash’ and its parental forms by the modern molecular-genetic methods - F. A. Davletov; K. P. Gaynullina; I. I. Akhmadullina (Зерновое хозяйство России)
The peas (Pisumsativum L.) is one of the most ancient and important plants in the world. It is a main leguminous crop with high content of protein in the Republic of Bashkortostan. It’s of urgent importance to develop new, more tolerant to diseases and pests, highly productive varieties to improve productivity of peas. The article gives the study results of the new highly productive variety of peas ‘Uldash’ and its parental forms (the varieties ‘Usach’ and ‘Kormovoy 5’) conducted in the laboratory for breeding and seed-growing of leguminous crops and in the laboratory for molecular-genetic expertise of the Baskirsky Research Institute of Agriculture. The developed variety ‘Uldash’ is characterized with drought tolerance, early maturity, resistance to lodging and seed fall. The variety was sent to variety testing in 2015. The article presents the estimation of the studied varieties on morpho-biological and economically valuable traits (length of stem, number of beans per plant, number of seeds per bean, 1000-seed weight, seed weight per plant). The molecular-genetic analysis of three microsatellite loci AA255, AA200, AB28 has been conducted. The SSR-markers have been used for estimation of genetic polymorphism of peas and they have shown high efficiency. The uniform distribution along the whole genome, co-dominant inheritance and a high level of polymorphism allow using them as a perfect system for the development of genetic markers. The data, obtained during the study, showed a possibility to apply microsatellite markers for the analysis of hybrid forms and genetic identification of the studied varietal samples.